Pajak Pusat Dan Pajak Daerah - Naya Salsabila; Adi Syahputra (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the role and comparative contribution of central and local taxes to economic development in Indonesia using a qualitative approach through library research. The data were obtained from various sources, including books, scientific journals, laws and regulations, and official government reports. The results indicate that central taxes have a more dominant contribution in financing national development through the state budget, particularly in infrastructure, education, and macroeconomic stability. Meanwhile, local taxes play an important role in supporting regional economic development through local revenue and enhancing fiscal independence. Therefore, strong synergy between central and local governments is needed to optimize tax revenue in supporting sustainable and equitable economic development